The alphabet theatre proudly presents the Z was zapped : a play in twenty-six acts - Van Allsburg, Chris (Houghton Mifflin, 1987)
Depicts how A was in an avalanche, B was badly bitten, C was cut to ribbons, and the other letters of the alphabet suffered similar mishaps.